How Raccoons Could Lead to the Disappearance of Native Crayfish in Central Italy - Tricarico, Elena; Ciampelli, Paola; De Cicco, Laura; Marsella, Sandro Aurelio; Petralia, Lorenzo; Rossi, Barbara; Zoccola, Antonio; Mazza, Giuseppe (Frontiers in Ecology and Evolution, 2021)
The white-clawed crayfish Austropotamobius pallipes complex populations are decreasing in the Foreste Casentinesi, Monte Falterona e Campigna National Park (Central Italy) for several factors, including illegal poaching, predatory fishes, drought, and invasive alien species. Recently, the Northern raccoon Procyon lotor has been reported for the area of the National Park and has started to predate on the white-clawed crayfish. The aim of the study was to update the distribution and population status of A. pallipes in the reserves, other sites of the National Park, and surrounding areas to assess the potential effects of the raccoon. Crayfish were sampled by hand or by traps in fourteen sites; sampled individuals were sexed and measured. Signs of raccoon presence (e.g. footprints and predated crayfish) were also recorded. Our study confirms the impact of raccoon on native crayfish: indeed, where the invasive mammal is present (six sites), crayfish disappeared or their populations have been dramatically reduced in number, with a size distribution skewed towards juveniles. In two sites, close to urban settlements, fresh footprints of P. lotor and predated specimens of A. pallipes were also observed. Populations of crayfish are still abundant or even increase compared to samplings conducted in the past where raccoon is absent (five sites). Urgent actions (e.g. control of raccoons, monitoring and restocking of A. pallipes populations if feasible and where possible) should be taken into account to guarantee the survival of this protected species.